Oral contraception following abortion: A systematic review and meta-analysis. Issue 27 (July 2016) - Che, Yan; Liu, Xiaoting; Zhang, Bin; Cheng, Linan
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Oral contraceptives (OCs) following induced abortion offer a reliable method to avoid repeated abortion. However, limited data exist supporting the effective use of OCs postabortion. We conducted this systematic review and meta-analysis in the present study reported immediate administration of OCs or combined OCs postabortion may reduce vaginal bleeding time and amount, shorten the menstruation recovery period, increase endometrial thickness 2 to 3 weeks after abortion, and reduce the risk of complications and unintended pregnancies. A total of 8 major authorized Chinese and English databases were screened from January 1960 to November 2014. Randomized controlled trials in which patients had undergone medical or surgical abortions were included. Chinese studies that met the inclusion criteria were divided into 3 groups: administration of OC postmedical abortion (group I; n = 1712), administration of OC postsurgical abortion (group II; n = 8788), and administration of OC in combination with traditional Chinese medicine postsurgical abortion (group III; n = 19, 707). In total, 119 of 6160 publications were included in this analysis. Significant difference was observed in group I for vaginal bleeding time ( P = 0.0001), the amount of vaginal bleeding ( P = 0.03), and menstruation recovery period ( P  < 0.00001) compared with the control groups. Group II demonstrated a significant difference in vaginal bleeding time ( P  < 0.00001), the amount of vaginal bleeding ( P = 0.0002), menstruation recovery period ( P  < 0.00001), and endometrial thickness at 2 ( P = 0.003) and 3 ( P  < 0.00001) weeks postabortion compared with the control group. Similarly, a significant difference was observed in group III for reducing vaginal bleeding time ( P  < 0.00001) and the amount of vaginal bleeding ( P  < 0.00001), shortening the menstruation recovery period ( P  < 0.00001), and increasing endometrial thickness 2 and 3 weeks after surgical abortion ( P  < 0.00001, all). Immediate administration of OCs postabortion may reduce vaginal bleeding time and amount, shorten the menstruation recovery period, increase endometrial thickness 2 to 3 weeks after abortion, and reduce the risk of complications and unintended pregnancies.